Thromboprophylaxis Use in Paediatric Inflammatory Bowel Disease: An International RAND Appropriateness Panel. (24th May 2022) - Torrente, Franco; Meade, Susanna; Benchimol, Eric I; de Ridder, Lissy; Croft, Nicholas M; Kammermeier, Jochen; Mack, David R; Klomberg, Renz C W; Turner, Dan; Wilson, David C; Martín-de-Carpi, Javier; Bronsky, Jiri; et al.
Abstract: Background and Aims: Thromboprophylaxis use in paediatric inflammatory bowel disease [IBD] is inconsistent. Current guidelines only support treating children with acute severe colitis with risk factors. We convened an international RAND panel to explore thromboprophylaxis in paediatric IBD inpatients in the context of new evidence. Methods: We convened a geographically diverse 14-person panel of paediatric gastroenterologists alongside supporting experts. An online survey was sent before an online meeting. Panellists were asked to rate the appropriateness of thromboprophylaxis in hospitalised paediatric IBD patients via 27 scenarios of varying ages, gender, and phenotype, with and without thrombotic risk factors. Anonymised results were presented at the meeting. A second modified survey was distributed to all panellists present at the meeting. Results from the second survey constitute the RAND panel results. The validated RAND disagreement index defined disagreement when ≥ 1. Results: The combined outcome of thromboprophylaxis being considered appropriate until discharge and inappropriate to withhold was seen in 20 of 27 scenarios, including: all patients with new-onset acute severe colitis; all flares of known ulcerative colitis, irrespective of risk factors except in pre-pubescent patients with limited disease and no risk factors; and all Crohn's patients with risk factors. Disagreement was seen in five scenarios regarding Crohn's without risk factors, where outcomes were already uncertain. Conclusions: RAND panels are an established method to assess expert opinion in areas of limited evidence. This work therefore constitutes neither a guideline nor a consensus; however, the findings suggest a need to re-evaluate the role of thromboprophylaxis in future guidelines.